APPLICATIONS ON DIFFERENTIAL SUBORDINATION INVOLVING LINEAR OPERATOR - Juma, A. R. S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
In the present paper, we introduce and investigate some subclasses of strongly close-to-convex functions associated with the linear operator of meromorphic pvalently functions and study several inclusion relationships with some properties of this operator.